A role for sugar transporters during seed development: Molecular characterization of a hexose and a sucrose carrier in fava bean seeds - Sauer, Norbert; et al. (The Plant Cell, 1997)
To analyze sugar transport processes during seed development of fava bean, we cloned cDNAs encoding one sucrose and one hexose transporter, designated VfSUT1 and VfSTP1, respectively. Sugar uptake activity was confirmed after heterologous expression in yeast. Gene expression was studied in relation to seed development. Transcripts were detected in both vegetative and seed tissues. In the embryo, VfSUT1 and VfSTP1 mRNAs were detected only in epidermal cells, but in a different temporal and spatial pattern. VfSTP1 mRNA accumulates during the midcotyledon stage in epidermal cells covering the mitotically active parenchyma, whereas the VfSUT1 transcript was specific to outer epidermal cells showing transfer cell morphology and covering the storage parenchyma. Transfer cells developed at the contact area of the cotyledonary epidermis and the seed coat, starting first at the early cotyledon stage and subsequently spreading to the abaxial region at the late cotyledon stage. Feeding high concentrations of sugars suppressed both VfSUT1 expression and transfer cell differentiation in vitro, suggesting a control by carbohydrate availability.